(untitled) (Research, Society and Development, 2022)
The crop-forest integration system (ILF) integrates the forestry and agricultural component. This study aimed to evaluate organic carbon stocks and soil physical attributes under a crop-forest integration system, in southwestern Minas Gerais. The study was carried out at the Experimental Farm of the Universidade do Estado de Minas Gerais, Academic Unit of Passos. The experimental design used was in randomized blocks, with three treatments and seven replications. The effect of this system on soil attributes was tested by means of analysis of variance. The effects of treatments were evaluated considering the position of row and between rows. When there was a significant effect (P<0.05) of treatment, the Tukey-Kramer test was performed at P<0.05 and between the test positions t and P<0.05, using the Physical attributes altered by the system ILP were soil density, total soil volume and temperature. The primary forest showed higher COS contents and stock than the other treatments. The total stock of COS showed no difference between the ILP system and the primary forest, indicating the sustainability of this production system.